Pôr o preto no branco: ideologias geográficas no romance Canaã, de Graça Aranha - Lira, Messias de [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The social relations on the lenses of science can reveal themselves under different languages and perspectives. In this way, it is understood that the literary analysis allows exploring geographical aspects by transfiguring a social reality into an element of the literary structure, enabling the investigation itself, as well as the functions that the work exerted or exerts on materiality. In this way, the analysis of the work Canaan captures the dynamics and social processes that organized ideologies linked to the construction of a national project. The analysis of the geographic ideologies presents in the work Canaã (1902), aims to understand certain concepts and expressions related to geographic analysis - such as landscape, race and territory - in the composition of a discourse of Brazilian national identity built on the characters. In order to demonstrate elements that were thought to the time the geographic space and the construction of the nation. For this purpose, we use the concepts of geographic ideologies and world view. Through both we can draw an interpretation of the speeches of the characters, so that they identify and demonstrate particularities of the Brazilian territorial formation, while approaching the historical movements of the time, which demonstrate the articulation between space, subject and work

As relações sociais sobre as lentes da ciência, podem se revelar sob diferentes linguagens e perspectivas. Dessa forma, entende-se que a análise literária permite explorar aspectos geográficos ao transfigurar uma realidade social em um elemento da estrutura literária, possibilitando a investigação em si, bem como das funções que a obra exerceu ou exerce sobre a materialidade. Dessa maneira, a análise da obra Canaã, capta as dinâmicas e processos sociais que organizaram ideologias ligadas à construção de um projeto nacional. A análise das ideologias geográficas presentes na obra Canaã (1902), tem como intuito, compreender determinados conceitos e expressões relativas à análise geográfica - tais como paisagem, raça e território - na composição de um discurso de identidade nacional brasileira construída nas personagens. De modo a demonstrar elementos que eram pensados à época o espaço geográfico e a construção da nação. Para tal propósito, utilizamos os conceitos de ideologias geográficas e visão de mundo. Através de ambos podemos traçar uma interpretação dos discursos das personagens, de modo que, identificamse e demonstram particularidades da formação territorial brasileira, ao passo que nos aproxima dos movimentos históricos da época, que demonstram a manifestam a articulação entre espaço, sujeito e obra
Keywords: Aranha, Graça 1868-1931; Geografia - Historia; Ideologia; Paisagens; Raças; Territorio nacional; Espaço em geografia; Geografia na literatura; Brasil